Investigating Optimism In Clouds Movie (2020): A Psychological Approach - Amar Ma'ruf; Syahara Dina Amalia (International Journal of English Linguistics, Literature, and Education (IJELLE), 2025)
This research explores how optimism is displayed in the movie Clouds (2020) by using Martin Seligman's optimism theory from Positive Psychology. The objectives of this study are (1) to evaluated of optimism reflected in the Clouds movie and (2) to indentify the impact on main character Zach. A qualitative method was used to study scenes and dialog from the movie. Data were taken from the movie and supported by books, journals, and related theories. The data were analyzed using Mile’s and Huberman’s (1994) model. The results showed 17 moments in the film that reflected three parts of optimism: permanence (8 data), personalization (5 data), and pervasiveness (4 data). Zach receives strong support from the people around him, especially his mother Laura, his best friend Sammy, and his girlfriend Amy. Their support helped him to stay strong, hopeful and confident in facing cancer. This finding is in line with Seligman's theory, which shows how positive thinking helps people to stay mentally strong during difficult times. The research also shows that the movie Clouds (2020) brings attention to important issues such as emotional support and mental health. It encourages people to think more about how movies can shape our understanding of optimism and well-being in everyday life.